Migraine in children and adults born preterm: A nationwide register linkage study. (May 2021) - Strang-Karlsson, Sonja; Alenius, Suvi; Näsänen-Gilmore, Pieta; Nurhonen, Markku; Haaramo, Peija; Evensen, Kari Anne I; Vääräsmäki, Marja; Gissler, Mika; Hovi, Petteri; Kajantie, Eero
Objective: Being born preterm is related to adverse health effects later in life. We studied whether preterm birth predicts the risk of migraine. Methods: In this nationwide register study, we linked data from six administrative registers for all 235, 624 children live-born in Finland (January 1987 to September 1990) and recorded in the Finnish Medical Birth Register. n = 228, 610 (97.0%) had adequate data and were included. Migraine served as primary outcome variable and was stringently defined as a diagnosis from specialised health care and/or ≥2 reimbursed purchases of triptans. We applied sex- and birth year-stratified Cox proportional hazard regression models to compute hazard ratios and confidence intervals (95% confidence intervals) for the association between preterm categories and migraine. The cohort was followed up until an average age of 25.1 years (range: 23.3–27.0). Results: Among individuals born extremely preterm (23–27 completed weeks of gestation), the adjusted hazard ratios for migraine was 0.55 (0.25–1.24) when compared with the full-term reference group (39–41 weeks). The corresponding adjusted hazard ratios and 95% confidence intervals for the other preterm categories were: Very preterm (28–31 weeks); 0.95 (0.68–1.31), moderately preterm (32–33 weeks); 0.96 (0.73–1.27), late preterm (34–36 weeks); 1.01 (0.91–1.11), early term (37–38 weeks); 0.98 (0.93–1.03), and post term (42 weeks); 0.98 (0.89–1.08). Migraine was predicted by parental migraine, lower socioeconomic position, maternal hypertensive disorder and maternal smoking during pregnancy. Conclusion: We found no evidence for a higher risk of migraine among individuals born preterm.